Peran E-business dalam Mendorong Praktik Green Banking di Sektor Keuangan yang Berkelanjutan - Dwi Putri Octavianni; Muhammad Iqbal Fasa (Yayasan Literasi Sains Indonesia, 2025)
The abstract of the study offers deep insight into the relationship between e-uinness and Green Banking, as well as technological roles in strengthening sustainability practices in the financial sector. E-bustics has become the main driver in implementing Green Banking practices. Through the use of information and communication technology, financial institutions can increase operational efficiency while reducing the environmental impact of their business activities. This study aims to explore the role of e-bust in promoting the application of Green Banking in Indonesia. By using a qualitative approach, it is hoped that this study can provide understanding of the integration of digital technology with environmentally friendly practices. The results from this study show that e-busting adoption not only helps financial institutions achieve sustainability goals, but also increases their competitiveness in the market. The resulting recommendations are expected to assist financial institutions in developing a more effective strategy to improve their operational sustainability. Thus, this study contributes a significant contribution to the understanding of how technological innovations can support transition to more sustainable and responsible business practices in Indonesia.